- #1

etotheipi

Gold Member

2019 Award

- 2,528

- 1,459

## Homework Statement:

- See below

## Relevant Equations:

- N/A

The apparent length of a rod is determined to be$$\tilde{L}(x_0) = \gamma L + \beta \gamma \sqrt{D^2 + (\gamma x_0 - \frac{L}{2})^2} - \beta \gamma \sqrt{D^2 + (\gamma x_0 + \frac{L}{2})^2}$$I am trying to determine expressions for ##\tilde{L}(x_0)## when ##x_0 \rightarrow -\infty## and ##x_0 \rightarrow \infty##. I rearranged it to$$\tilde{L} = \gamma L + \beta \gamma (\gamma x_0 - \frac{L}{2})\sqrt{1+\frac{D^2}{(\gamma x_0 -\frac{L}{2})^2}} - \beta \gamma (\gamma x_0 + \frac{L}{2})\sqrt{1+\frac{D^2}{(\gamma x_0 +\frac{L}{2})^2}}$$And it would then seem in both cases, since the square roots both approach 1 in both limits, that$$\tilde{L}(x_0 \rightarrow -\infty) = \tilde{L}(x_0 \rightarrow \infty)= \gamma L(1-\beta)$$However it is noted in the solution manual that in fact $$\tilde{L}(x_0 \rightarrow -\infty) =\gamma L(1+\beta)$$ and $$\tilde{L}(x_0 \rightarrow \infty) =\gamma L(1-\beta)$$What have I missed? Thanks!